Effect of surface modification of BiFeO3 on the dielectric, ferroelectric, magneto-dielectric properties of polyvinylacetate/BiFeO3 nanocomposites - O. P. Bajpai; J. B. Kamdi; M. Selvakumar; S. Ram; D. Khastgir; S. Chattopadhyay (eXPRESS Polymer Letters, 2014)
Bismuth ferrite (BiFeO3) is considered as one of the most promising materials in the field of multiferroics. In this work, a simple green route as well as synthetic routes has been used for the preparation of pure phase BiFeO3. An extract of Calotropis Gigantea flower was used as a reaction medium in green route. In each case so formed BiFeO3 particles are of comparable quality. These particles are in the range of 50–60 nm and exhibit mixed morphology (viz., spherical and cubic) as confirmed by TEM analysis. These pure phase BiFeO3 nanoparticles were first time surface modified effectively by mean of two silylating agent’s viz., tetraethyl orthosilicate (TEOS) and (3-Aminopropyl)triethoxysilane (APTES). Modified and unmodified BiFeO3 nanoparticles were efficiently introduced into polyvinylacetate (PVAc) matrix. It has been shown that nanocomposite prepared by modified BiFeO3 comprise superior dispersion characteristics, improved ferroelectric properties and favorable magneto-dielectric properties along with excellent wettability in compare to nanocomposite prepared by unmodified BiFeO3. These preliminary results demonstrate possible applications of this type of nanocomposites particularly in the field of multiferroic coating and adhesives.